Neonatal Testicular Torsion with Hydrocele: A Case Report Underscoring the Need for Early Recognition and Management - Kareem Omran; Sameh Ali Ali; Ehsan Ahmad; Hilal Matta; Wissam Jamal Al Tamr (Case Reports in Surgery)
Neonatal testicular torsion (NTT) is a rare but significant condition occurring within the first 30-day postbirth, leading to vascular compromise and potential testicular loss. This paper presents a case of NTT detected incidentally in a neonate with bilateral hydrocele, emphasizing the challenge of early diagnosis and management complexities. The infant underwent surgical intervention involving detorsion and bilateral orchiopexy but eventually required right orchiectomy due to necrosis. The paper highlights the prevalence of NTT in conjunction with hydrocele and stresses the importance of parent education and vigilant follow-up. Various diagnostic methods, primarily ultrasonography, and a range of management strategies are discussed, considering factors such as salvage potential, risk to the contralateral testicle, and surgical intervention’s risks and benefits. The paper argues for individualized management, taking into account specific neonate conditions and parental preferences, underlining the essential role of informed and empathetic consultation. The case reinforces the urgent need for increased awareness, early detection, and carefully considered therapeutic approaches to prevent devastating outcomes like infertility and the necessity for lifelong hormone supplementation.